1984
DOI: 10.1111/1523-1747.ep12260985
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Chemotactic Lipoxygenase Products of Arachidonate Metabolism in Psoriatic Skin

Abstract: Skin biopsies and scale extracts from 22 patients with psoriasis were examined for the presence of chemotactic lipoxygenase products of arachidonate metabolism. Heat-stable leukocyte chemotactic activity in aqueous extracts of 2-mm punch biopsies from involved and uninvolved patient skin was significantly elevated, compared to healed psoriatic skin and to skin of normal controls. Ether extracts (pH 3.0) from 13 mg of psoriatic scales contained a mean chemotactic activity corresponding to that of leukotriene B4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(29 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…It can exert its e ects on cells and tissues by increasing aggregation and release of lysosomal enzymes, stimulating superoxide anion production in neutrophils, increasing interleukin-2 (IL-2) release and receptors in lymphocytes and enhancing vascular permeability in tissues (Ford-Hutchinson, 1990). Psoriasis, in¯ammatory bowel disease (IBD), rheumatoid arthritis and mostly asthma have all been associated with the potent in¯ammatory properties of LTB 4 (Davidson et al, 1983;Brain et al, 1984;Grabbe et al, 1984;Sharon & Stenson, 1984). Inhibitors of 5-LO and 5-LO activating protein (FLAP) have been developed as therapeutic agents for the treatment of asthma and their e ects on psoriasis and IBD have also been studied (Larsen & Jackson, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…It can exert its e ects on cells and tissues by increasing aggregation and release of lysosomal enzymes, stimulating superoxide anion production in neutrophils, increasing interleukin-2 (IL-2) release and receptors in lymphocytes and enhancing vascular permeability in tissues (Ford-Hutchinson, 1990). Psoriasis, in¯ammatory bowel disease (IBD), rheumatoid arthritis and mostly asthma have all been associated with the potent in¯ammatory properties of LTB 4 (Davidson et al, 1983;Brain et al, 1984;Grabbe et al, 1984;Sharon & Stenson, 1984). Inhibitors of 5-LO and 5-LO activating protein (FLAP) have been developed as therapeutic agents for the treatment of asthma and their e ects on psoriasis and IBD have also been studied (Larsen & Jackson, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…12-HETE is the predominant eicosanoid found greatly up-regulated in psoriasis, whilst increases in the levels of PGE 2 and PGF 2α are less prominent [3,96] and 15-HETE is decreased in uninvolved psoriatic skin compared to healthy epidermis [97]. Chiral analysis has revealed the prevalence of 12R-HETE in psoriatic scales pointing at the involvement of 12R-LOX [75].…”
Section: Psoriasismentioning
confidence: 99%
“…CYP isozymes can mediate the oxidation of eicosanoids, as suggested by the co-localisation of COX-2, mPGES-1 and CYP4F8 in psoriatic lesions leading to oxidation of PGE 2 [100]. In the past there has been a strong interest in the role of 5-LOX-derived leukotrienes in psoriasis and other skin disorders [96,101]. However, the low 5-LOX activity in epidermal keratinocytes indicates that these eicosanoids may be formed through transcellular pathways involving dermally infiltrating neutrophils [102], a consequence of the high concentration of the 12-HETE, a potent chemotactic eicosanoid highly prevalent in psoriatic skin.…”
Section: Psoriasismentioning
confidence: 99%
“…Elevated levels of non-esterified arachidonic acid (Hammarstrdm et al, 1975), lipoxygenase products of arachidonic acid oxidation (Grabbe et al, 1984;Camp et al, 1983b;Brain et al, 1984) and epidermal phospholipase A2 activity (Forster et al, 1983) have been reported in the skin of psoriasis patients. Recently, Cunningham et al (1985) have demonstrated that arachidonic acid applied topically to human forearm skin under occlusion induces an erythematous reaction.…”
Section: Introductionmentioning
confidence: 99%